Analysis of Core Technologies and Implementation Services for Smart City - et. al., Jae-saeng Kim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smart City Platform is a software that optimally allocates resources and provides services to citizens by utilizing ICT technologies such as artificial intelligence, IoT, virtual reality, augmented reality, and 5G mobile communication to solve various urban problems occurring in the city.In order to implement the Smart City environment, basic platform technologies such as artificial intelligence, big data, network, Internet of Things(IoT) and Cloud computing are essential.In this paper, we used the big data analysis tool ‘BigKinds’ to lookup the topic 'Smart City Technology' and 'Smart City IoT' in news, editorials and quotations. After analyzing them, we then derived the core technologies needed in building a Smart City. Furthermore, we introduced the concept of the basic Smart City technologies and then deduced implications and drew a conclusion by analyzing both the local and foreign Smart City construction services. In addition, it compared and analyzed the core technologies for supporting services in various smart cities.The Smart City’s basic technologies and service analysis can be utilized by the local government to effectively establish policies and technology strategies in the Smart City industry.